Skipping Breakfast Among Young Adults Affects the Incidence of Overweight and Obesity - Amalina Shabrina; Farah Islamiyah; Widia Susanti (Universitas Muhammadiyah Surakarta, 2023)
Introduction: It has been established that dietary habits are associated with nutritional status. However, few studies have evaluated dietary habits among young adults in college. College students represent a period of nutritional vulnerability due to dietary transition from home to college. This cross-sectional study evaluated the dietary habits, including breakfast habit, frequency of snacking, and frequency of meals, with the incidence of overweight and obesity among young adults. Method: Weight and height were measured using digital scale and microtoise, respectively. Body mass index (BMI) was then calculated and classified based on the Indonesian cut-off points. Dietary habits were collected through a questionnaire. Subjects were selected using simple random sampling. Chi-square test was performed using SPSS. Results: From the total 99 subjects aged 18-22 years old, 15.2% subjects were identified as overweight (BMI >25.0-27.0) and 17.2% as obese (BMI >27.0). Irregular breakfast habit <6x/week was associated with overweight and obesity among young adults (p=0.002), while frequency of snacking and meals were not associated with overweight and obesity (p>0.05). Conclusion: Overweight and obesity among young adults were associated with irregular breakfast habit, but not with frequency of snacking and meals. Our results suggested that young adults in college should regularly consume breakfast to avert the incidence of overweight and obesity.